2021
DOI: 10.1016/j.wneu.2020.10.171
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the Surgical Team Toward Artificial Intelligence in Neurosurgery: International 2-Stage Cross-Sectional Survey

Abstract: Background Artificial intelligence (AI) has the potential to disrupt how we diagnose and treat patients. Previous work by our group has demonstrated that the majority of patients and their relatives feel comfortable with the application of AI to augment surgical care. The aim of this study was to similarly evaluate the attitudes of surgeons and the wider surgical team toward the role of AI in neurosurgery. Methods In a 2-stage cross sectional survey, an initial open-que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…As such, telemedicine can be used for follow-up visits which would have required in-person clinic visits, remote diagnosis of postsurgery complications, as well as continued routine monitoring [89] . In comparison, the use of AI in postoperative care and follow-up of neurosurgery is less agreeable among surgeons and surgical teams compared to other usages such as pre-operative planning and image interpretation [90] .…”
Section: The Role Of Ai In Pre- Intra- and Postoperative Phases Of Neurosurgerymentioning
confidence: 96%
See 1 more Smart Citation
“…As such, telemedicine can be used for follow-up visits which would have required in-person clinic visits, remote diagnosis of postsurgery complications, as well as continued routine monitoring [89] . In comparison, the use of AI in postoperative care and follow-up of neurosurgery is less agreeable among surgeons and surgical teams compared to other usages such as pre-operative planning and image interpretation [90] .…”
Section: The Role Of Ai In Pre- Intra- and Postoperative Phases Of Neurosurgerymentioning
confidence: 96%
“…Recent qualitative studies have shown that while patients and their relatives welcome the use of AI in neurosurgery and find it acceptable, they were reluctant to be treated by fully autonomous neurosurgeries and would like to have neurosurgeons to ultimately remain in control [104] . Similarly, most neurosurgeons welcome the use of AI in neurosurgery [90] , so there is a consensus among neurosurgeons and patients on the use of AI in neurosurgery. Multiple studies have shown that the combination of AI with clinicians improved clinical decision making compared to clinicians or AI alone [50] , [70] , [105] , [106] .…”
Section: Challenges Associated With Using Ai In Neurosurgerymentioning
confidence: 99%
“…The widespread introduction of AI in brain tumour surgery will require the addition of AI to the neurosurgical and oncological teaching curriculum. At present, neurosurgical teaching curricula has little focus on AI as a teaching subject, with research demonstrating that one third have no prior knowledge of the subject [ 203 ]. As clinicians, we must be expected to understand the mechanisms of the technology we operate, such that black-box systems are not perpetuated.…”
Section: Barriers Evaluation and Ethicsmentioning
confidence: 99%
“…Concerns regarding clinician displacement and replacement by AI robotics —the “human-vs.-machine” paradigm—are unlikely to bear truthful in the near future, and indeed, research has identified that neurosurgeons are generally comfortable with greater integration of AI [ 8 , 203 ]. Humans and ML models are likely to work in tandem with one another, rather than be fully replaced.…”
Section: Barriers Evaluation and Ethicsmentioning
confidence: 99%
“…The survey was created using Google Forms. A link to the survey was sent to healthcare professionals by informing healthcare professionals in our own network in Finland via Facebook and using SurveyCircle scientific survey service 10 . No individual requests to complete the survey were sent.…”
Section: Survey Design and Participantsmentioning
confidence: 99%